Perbandingan Rangka Atap Baja Ringan dan Tipe Single Beam Gedung Fakultas Pendidikan Universitas Tribhuwana Tunggadewi - Baga, Ferdinand Ardinata ; Suhudi; Arifianto, Andy Kristafi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
The development of technology in the era of the moderan brought changes both to the progress in construction and infrastructure development. The use of mild steel in the building of the Faculty of education at the University campus TribhuwanaTunggadewi on roof frame structure has several advantages: light weight, homogeneous material, resistant to termites, stainless, not rotted, and hold against the weather, as well as the installation of a relatife easy and fast. The purpose of the research this time to find out the cost of light steel roof frame structure with a single beam-type structures as well as knowing the method implementation on the cost structure of roof type single beam with light steel roof trunk. The research method used was the real survey methods based on SNI and candy PU. Based on the results of the comparative analysis of srtuktur order of mild steel roof with roof structure type single beam, then the data for light steel roof frame earned Rp 29,470,000.00 While the data for single beam-type structures are obtained at Rp. RP 54.606.000. And the method of implementation for the job order mild steel roof with roof structure type single beam obtained results that structure type single beam easier and quicker and shorter time.